Dioxin-like activities in serum across European and Inuit populations - Zvyezday Valentyna; Pedersen Henning S; Toft Gunnar; Spanò Marcello; Bizzaro Davide; Manicardi Gian-Carlo; Giwercman Aleksander; Hagmar Lars; Lindh Christian H; Andersen Birgitte S; Long Manhai; Bonde Jens; et al. (BMC, 2006)
Abstract Background Persistent organic pollutants (POPs) such as polychlorinated dibenzo-p-dioxins/furans, polychlorinated biphenyls (PCBs) and organochlorine pesticides can cause a series of adverse effects on e.g. reproduction in animals and humans, many of which involve the aryl hydrocarbon receptor (AhR). The aim of the present study was to compare the integrated serum level of AhR mediated activity among European and Inuit populations, and evaluate whether the activity was associated to the selected POP markers, 2,2',4,4',5,5'-hexachlorobiphenyl (CB-153) and 1,1-dichloro-2,2-bis(p-chlorophenyl)-ethylene (p,p'-DDE). Methods The study included 338 males from Greenland (Inuit's), Sweden, Warsaw (Poland) and Kharkiv (Ukraine). The AhR transactivity of serum extracts alone (AhRag) and competitive AhR activity (AhRcomp) upon co-exposure with 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) were determined in the lipophilic serum fraction containing the POPs using the AhR mediated luciferase reporter Hepa1.12cR cell assay. Results The European groups showed higher median level of AhR-TEQ (TCDD toxic equivalents) compared to the Inuit's, whereas higher incidence of Inuits sample further induced AhRcomp activity. Neither AhRag nor AhR-TEQ were correlated to CB-153 or p,p'-DDE for any of the study groups. Multiple regressions showed a significant heterogeneity of association between the CB-153 and the AhRcomp across the study groups, and accordingly a negative association between AhRcomp and CB-153 was found for the Kharkiv group. Conclusion No consistent correlation between AhR activities and two POP markers was found. Although the difference of AhRag between European and Inuit men could not be explained by CB-153 or p,p'-DDE levels alone, we believe that the variation of AhR serum activity reflects different pattern of POP exposure, genetics and/or life style factors.